2017
DOI: 10.1177/0363546517741465
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Allograft Transplantation of the Knee in Patients Aged 40 Years and Older

Abstract: A higher failure rate was found in this series of patients aged ≥40 years who were treated with OCA as compared with other studies of younger populations. However, for select older patients, OCA can be a good midterm treatment option for cartilage defects of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 36 publications
6
77
0
Order By: Relevance
“… 42 OCA has shown excellent clinical results throughout the knee in a variety of patient populations. 2 , 6 , 10 , 37 , 43 …”
Section: Discussionmentioning
confidence: 99%
“… 42 OCA has shown excellent clinical results throughout the knee in a variety of patient populations. 2 , 6 , 10 , 37 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…They have provided a series of papers looking at subgroups, showing that results of OCA are no worse in patients who have had anterior cruciate ligament reconstruction (ACLR) [ 64 ] or in those with Body Mass Index (BMIs) over 30 (graft survival 83% at 5 years) [ 49 ]. They also found that results in patients aged over 40 (mean age 48, range 40–63 years) were also good, with graft survival 73% at 4 years [ 65 ].…”
Section: Evidence: Primary Studiesmentioning
confidence: 99%
“…Eighty percent of the patients reported satisfactory results at a median follow-up of 6.6 years; the reported survivorship was 80% at 5 years and 70% at 10 years. Wang et al 86 treated 54 patients aged >40 years with OCA to treat femoral and patella osteochondral defects. They reported higher failure and reoperation rates compared with other series of younger patients and a 4-year survivorship rate of 73%.…”
Section: Literature Reviewmentioning
confidence: 99%